Genetic inhibition of nuclear factor of activated T-cell c2 prevents atrial fibrillation in CREM transgenic mice . Issue 13 (14th October 2021) - Ni, Li; Lahiri, Satadru K; Nie, Jiali; Pan, Xiaolu; Abu-Taha, Issam; Reynolds, Julia O; Campbell, Hannah M; Wang, Haihao; Kamler, Markus; Schmitz, Wilhelm; Müller, Frank Ulrich; Li, Na; et al.
Abstract: Aims: Abnormal intracellular calcium (Ca 2+ ) handling contributes to the progressive nature of atrial fibrillation (AF), the most common sustained cardiac arrhythmia. Evidence in mouse models suggests that activation of the nuclear factor of activated T-cell (NFAT) signalling pathway contributes to atrial remodelling. Our aim was to determine the role of NFATc2 in AF in humans and mouse models. Methods and results: Expression levels of NFATc1–c4 isoforms were assessed by quantitative reverse transcription–polymerase chain reaction in right atrial appendages from patients with chronic AF (cAF). NFATc1 and NFATc2 mRNA levels were elevated in cAF patients compared with those in normal sinus rhythm (NSR). Western blotting revealed increased cytosolic and nuclear levels of NFATc2 in AF patients. Similar findings were obtained in CREM-IbΔC-X transgenic (CREM) mice, a model of progressive AF. Telemetry ECG recordings revealed age-dependent spontaneous AF in CREM mice, which was prevented by NFATc2 knockout in CREM:NFATc2 –/– mice. Programmed electrical stimulation revealed that CREM:NFATc2 –/– mice lacked an AF substrate. Morphometric analysis and histology revealed increased atrial weight and atrial fibrosis in CREM mice compared with wild-type controls, which was reversed in CREM:NFATc2 –/– mice. Confocal microscopy showed an increased Ca 2+ spark frequency despite a reduced sarcoplasmic reticulum (SR) Ca 2+ load in CREM mice compared with controls, whereas these abnormalities were normalized in CREM:NFATc2 –/– mice. Western blotting revealed that genetic inhibition of Ca 2+ /calmodulin-dependent protein kinase II-mediated phosphorylation of S2814 on ryanodine receptor type 2 (RyR2) in CREM:RyR2-S2814A mice suppressed NFATc2 activation observed in CREM mice, suggesting that NFATc2 is activated by excessive SR Ca 2+ leak via RyR2. Finally, chromatin immunoprecipitation sequencing from AF patients identified Ras and EF-hand domain-containing protein (Rasef) as a direct target of NFATc2-mediated transcription. Conclusion: Our findings reveal activation of the NFAT signalling pathway in patients of Chinese and European descent. NFATc2 knockout prevents the progression of AF in the CREM mouse model. Graphical Abstract: